2014
DOI: 10.1186/1471-2474-15-397
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of the delphi definitions of low back pain prevalence (German DOLBaPP)

Abstract: BackgroundAssessed dimensions of low back pain (LBP) vary in prevalence studies. This may explain the heterogeneity in frequency estimates. To standardize definitions of LBP, an English consensus with 28 experts from 12 countries developed the “Delphi Definitions of Low Back Pain Prevalence” (DOLBaPP). The optimal definition and the shorter minimal definition with the related questionnaires for online, paper, and face-to-face use and telephone surveys are suitable for population-based studies. The definitions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 25 publications
1
11
2
1
Order By: Relevance
“…Some participants had di culty understanding question 6 about time since previous LBP episode and participants in the German study suggested to remove the negation in the question and to shorten the sentence [10]. As for the German version [10], most participants needed less than 5 minutes to complete the questionnaire. Furthermore, participants suggested to add questions about the cause of the pain, the duration of the problems, previous LBP episodes, physical activity, and LBP management and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some participants had di culty understanding question 6 about time since previous LBP episode and participants in the German study suggested to remove the negation in the question and to shorten the sentence [10]. As for the German version [10], most participants needed less than 5 minutes to complete the questionnaire. Furthermore, participants suggested to add questions about the cause of the pain, the duration of the problems, previous LBP episodes, physical activity, and LBP management and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although these erroneous answers had no impact on the prevalence rates and all responses were plausible, they might be avoided. If using the paper questionnaire, an instruction could be added explaining that if participants answer "no" to question 1 on LBP, they can skip to answer the questions 2, 5, 6 and 7, as also suggested by Leonhardt et al [10]. In case an online form is used, inbuilt data validation rules can ensure that people get the right questions based on the previous answers [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optamos pela metodologia citada por Beaton et al 13 por ser de reconhecimento internacional e citada em grande parte dos estudos metodológicos pesquisados 17,18 . No presente estudo, o processo de tradução e adaptação transcultural cumpriu todas as etapas necessárias para um resultado satisfatório.…”
Section: Discussionunclassified